Adaptive functioning following pediatric traumatic brain injury: Relationship to executive function and processing speed - Shultz, Emily (Neuropsychology, 2016)
OBJECTIVE: Pediatric traumatic brain injury (TBI) may affect children’s ability to perform everyday tasks (i.e., adaptive functioning). Guided by the American Association for Intellectual and Developmental Disabilities (AAIDD) model, we explored the association between TBI and adaptive functioning at increasing levels of specificity (global, AAIDD domains, and subscales). We also examined the contributions of executive function and processing speed as mediators of TBI’s effects on adaptive functioning. METHOD: Children (ages 8–13) with severe TBI (STBI; n=19), mild-moderate TBI (MTBI; n=50), or orthopedic injury (OI; n=60) completed measures of executive function (TEA-Ch) and processing speed (WISC-IV) an average of 2.7 years post-injury (SD = 1.2; range: 1–5.3). Parents rated children’s adaptive functioning (ABAS-II, BASC-2, CASP). RESULTS: STBI had lower global adaptive functioning (η(2) = .04–.08) than the MTBI and OI groups, which typically did not differ. Deficits in the STBI group were particularly evident in the social domain, with specific deficits in social participation, leisure, and social adjustment (η(2) = .06–.09). Jointly, executive function and processing speed were mediators of STBI’s effects on global adaptive functioning and in conceptual and social domains. In the STBI group, executive function mediated social functioning, and processing speed mediated social participation. CONCLUSIONS: Children with STBI experience deficits in adaptive functioning, particularly in social adjustment, with less pronounced deficits in conceptual and practical skills. Executive function and processing speed may mediate the effects of STBI on adaptive functioning. Targeting adaptive functioning and associated cognitive deficits for intervention may enhance quality of life for pediatric TBI survivors.